Replication of Salmonella enterica serovar Typhimurium in RAW264.7 Phagocytes Correlates With Hypoxia and Lack of iNOS Expression - Wrande, Marie; Vestö, Kim; Puiac Banesaru, Speranta; Anwar, Naeem; Nordfjell, Johan; Liu, Lifeng; McInerney, Gerald M.; Rhen, Mikael (Frontiers in Cellular and Infection Microbiology, 2020)
Salmonella infection associates with tissue hypoxia, while inducible nitric oxide synthase (iNOS), relying for its activity on molecular oxygen, stands as a central host defence measure in murine salmonellosis. Here, we have detailed hypoxia and iNOS responses of murine macrophage-like RAW264.7 cells upon infection with Salmonella enterica serovar Typhimurium. We noted that only a proportion of the infected RAW264.7 cells became hypoxic or expressed iNOS. Heavily infected cells became hypoxic, while in parallel such cells tended not to express iNOS. While a proportion of the infected RAW264.7 cells revealed shutdown of protein synthesis, this was only detectable after 12 hours post infection and after iNOS expression was induced in the cell culture. Our data implicate an intrinsic heterogeneity with regard to hypoxia and iNOS expression, in a cell culture-based infection setting.